1981
DOI: 10.1161/01.res.48.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitroglycerin on regional myocardial ischemia induced by atrial pacing in dogs.

Abstract: SUMMARYThe exact mechanism or mechanisms by which nitroglycerin exerts its beneficial effect on pacing-induced regional myocardial ischemia has not been ellucidated previously. In an open-chest, anesthetized canine preparation a fixed, flow limiting stenosis was applied to the left anterior descending (LAD) coronary artery and heart rate was increased by atrial pacing. Mass spectrometry was used to measure myocardial oxygen (Pmo 2 ) and carbon dioxide (Pmco 2 ) tensions. Myocardial blood flow was measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In our present studies nitroglycerine reduced STsegment elevation in the endocardium more than it did in the epicardium. This accords with the finding that nitroglycerine increases oxygen tension in the endocardium without affecting that in the epicardium (Winbury, 1971) and with the observation of Gerry et al, (1981) that nitroglycerine reduces the elevated subendocardial Pco2 tension in the ischaemic area. This speaks in favour either of a selective arteriolar dilatation by nitroglycerine in the subendocardium or of a preferential effect on the transmural arteries (Winbury, 1971;Weiss, Howe & Winbury, 1973).…”
Section: Discussionsupporting
confidence: 89%
“…In our present studies nitroglycerine reduced STsegment elevation in the endocardium more than it did in the epicardium. This accords with the finding that nitroglycerine increases oxygen tension in the endocardium without affecting that in the epicardium (Winbury, 1971) and with the observation of Gerry et al, (1981) that nitroglycerine reduces the elevated subendocardial Pco2 tension in the ischaemic area. This speaks in favour either of a selective arteriolar dilatation by nitroglycerine in the subendocardium or of a preferential effect on the transmural arteries (Winbury, 1971;Weiss, Howe & Winbury, 1973).…”
Section: Discussionsupporting
confidence: 89%
“…When increased blood flow is adequate to meet the increased oxygen demands, myocardial oxygen tension will be maintained. If the increase in blood flow is sufficient, myocardial oxygen tension will decrease (Gerry et al, 1981). In this clinical study, myocardial oxygen tension decreased in the revascularized regions in the early postoperative days.…”
Section: Discussionmentioning
confidence: 63%
“…At a constant Po2 level, over a pH range of 7.2-7.9, differences in oxygen current in the various solutions were within 0.2%. This observation is in agreement with the findings of others (Gerry et af., 1981;Horvat et af., 1972;Hultgren et af., 1971).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a linear correlation between the magnitude of ST segment displacement obtained from epicardial maps and increases in heart rate in anaesthetised dogs with an occluded coronary artery.32 In dogs in whom coronary arteries have been constricted slowly over a period of time it has been shown that the normal increases in myocardial blood flow are drastically reduced in the subendocardial region supplied by the occluded arteries and that this reduction is dependent not only on the coronary perfusion pressure but also on the increases in heart rate and in local extravascular coronary resistance in association with augmented left ventricular enddiastolic pressure. [33][34][35][36] Several studies have shown that the degree of ST segment displacement correlates with the severity of reduction in myocardial blood flow3740 and with the degree of reduction in myocardial oxygen tension.41-43 Thus, from this evidence there should be some relation between ST segment depression, representing the degree of ischaemia (or lowered blood flow and oxygen tension) and heart rate; and the relation should be roughly linear. In the event, the ST/HR slope was surprisingly linear, that is the confidence limits around the regression lines were very small (see Ranges ofmaximal ST/HR slope One remarkable finding in the present investigation is that adjacent ranges of the maximal ST/HR slopes, each range correlating with insignificant, single, double, or triple vessel disease, have shown no overlap; the limits of adjacent ranges are quite separate.…”
Section: Possible Explanation Of Resultsmentioning
confidence: 99%